The Impact of Pseudostuttering Experiences on SLT students' Learning. (30th June 2015) - Tobin, L.; Lyons, R.
Abstract: Studies have shown that a significant number of Speech and Language Therapystudents report feeling less competent in the area of fluency. In light of this, a small number ofresearchers have reported that participation in a pseudo-stuttering exercise can enhancefluency modules and be a beneficial learning experience for Speech and Language Therapystudents. However, there is limited research to support this claim. Aim: To investigate the impact of a pseudo-stuttering experience on students' learning and theimplications for future clinical practice. This study used a qualitative methodology to facilitate an in-depth exploration of theexperiences of the participants. Two focus groups were conducted in which a total of 16 SLTstudents discussed their experiences. The focus groups were transcribed and coded with theaid of NVivo9 software. The data was analysed using principles of grounded theory. Analysis of the data identified three themes relating to the students' experiences ofpseudo-stuttering: Stepping into their shoes, Learning from experience and Implications forclinical practice. The students reported that their experience was not truly reflective of a PWS'sexperience. Nonetheless, they considered it as an opportunity to "Step into someone else'sshoes" which resulted in reports of increased empathy for PWS by some. Empathy has beenshown to facilitate the development of positive client-clinician relationships which in turn impactson therapy outcomes. The participants identified practical changes they will make to clinicalpractice following the experience. The findings suggest that participation in a pseudo-stuttering exercise can be avaluable learning tool for SLT students. Furthermore, this study considered important ethicalissues that previous research has overlooked.